The case for Biblical Archaeology: uncovering the historical record of God's Old Testament people - Currid, John D. (P&R Publishing, 2020)
"We gain encouragement and helpful background to Scripture in studying the land of the Bible (the "fifth gospel"). Archaeologist and biblical scholar John Currid overviews areas of inquiry and discovery"--